Employees’ Participation in Decision Making (PDM): a literature survey - Maslina Mohammed Shaed; Suraiya Ishak; Zaimah Ramli (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Contemporary organizations are forced to find ways to be more flexible and adaptive in order to stay competitive, and the increased importance of employees cannot be over-emphasised. This is reflected in the growing recognition of the employees’ participation in the organisational decision making process (PDM). This study examined the question of employees’ PDM as studied and deliberated in the literature. A total of 32 published articles from year 2010-2014 covering 24 variables provided the basis of this inquiry. The findings revealed that variables that had positive correlations with PDM were gender, education level, job experiences, organizational performance, job satisfaction, job performance, job commitment, perceived supervisor support, perceived organizational support, attitude, psychological ownership, self-efficacy, training, leadership, trust, motivation and productivity. All this reiterated the fact that employees’ PDM was one of the effective tools in enhancing positive outcomes for organisations, and should therefore be given due priority in organisational management.